Oddziaływanie huty CMC Zawiercie S.A. na środowisko, ze szczególnym uwzględnieniem gospodarki odpadami - Nyga, Katarzyna (My University, 2011)
Iron and steel metallurgical industry, along with related sectors, fulfill an important function in the economical development of the country. The evidence for this may be its significant impact on the successful execution of major infrastructure and construction projects, as well as consumer goods production. The development of this industry is related with the growth of competitiveness, and on the other side, environmental protection requirements. This thesis presents above mentioned problems on example of CMC Zawiercie S.A. steel mill. An environmental impact of the plant, as well as the waste management system, were main issues. During the investigation it was found that the plant affects all components of the environment, however, this impact has been local. In turn, the waste management was considered to be full settled.

Hutnictwo żelaza i stali, wraz z branżami pokrewnymi, pełni istotną rolę w rozwoju gospodarczym kraju. Przejawem tego zjawiska może być jego wpływ na przeprowadzanie projektów infrastrukturalnych, budowlanych, a także produkcję dóbr konsumpcyjnych. Zauważalny, zwłaszcza w ostatnim okresie, rozwój tej gałęzi przemysłu związany jest zarówno ze wzrostem konkurencyjności, jak i wymaganiami odnośnie ochrony środowiska. W pracy przedstawiono powyższe kwestie na przykładzie huty CMC Zawiercie S.A., skupiając się zwłaszcza na zagadnieniu jej oddziaływania na środowisko, a także zobrazowaniu systemu gospodarki odpadami funkcjonującego w zakładzie. W toku badań stwierdzono, iż zakład ten wpływa na wszystkie komponenty środowiska, jednak jest to problem lokalny. Gospodarkę odpadami uznano za w pełni uregulowaną.
Environmental impact of the CMC Zawiercie S.A. steel miil, with special consideration of waste management
Keywords: huta żelaza; elektryczny piec łukowy; emisje do środowiska; gospodarka odpadami; steel mill; electric arc furnace; emissions into the environment; waste management